2003
DOI: 10.1111/1469-8986.00114
|View full text |Cite
|
Sign up to set email alerts
|

Attention to external stimuli during wakefulness and sleep: Evoked 40‐Hz response and N350

Abstract: Changes of two components of the auditory event-related potential, the evoked 40-Hz response and the N350, were studied during different stages of wakefulness and sleep. The evoked 40-Hz response has been proposed to represent an attention-modulating mechanism; the N350 seems to reflect an inhibitory process associated with reduced information processing. Because recent literature suggests that both components reflect opposite mechanisms, an inverse relationship was expected. Ten participants were presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…That is, N350 could emerge during waking conditions if a stimulus is truly ignored, corresponding to the filtering of irrelevant stimuli. The N2 early of the current study could correspond to the N350 observed by Kallai et al [18] during wakefulness and sleep. Thus, the N2 in the responses to the standard stimuli of the young participants could reflect the more effective inhibition of the processing of irrelevant information, whereas the lack of N2 in the elderly could be interpreted as a decrease in the capability to suppress the processing of irrelevant stimuli.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…That is, N350 could emerge during waking conditions if a stimulus is truly ignored, corresponding to the filtering of irrelevant stimuli. The N2 early of the current study could correspond to the N350 observed by Kallai et al [18] during wakefulness and sleep. Thus, the N2 in the responses to the standard stimuli of the young participants could reflect the more effective inhibition of the processing of irrelevant information, whereas the lack of N2 in the elderly could be interpreted as a decrease in the capability to suppress the processing of irrelevant stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…Selective attention tasks also require the participant to ignore or blank out unimportant information actively. The initial belief that N350 could be recorded only during sleep but not in the waking state was disproved by a recent study [18]. ERP responses were recorded during different stages of wakefulness and sleep, while participants were reading or lying awake in bed, and during light sleep, slow wave sleep and rapid eye movement sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the amplitude of N350 was larger at or near the time of sleep onset (Ornitz et al, 1967) and was larger during light sleep relative to SWS (Kallai et al, 2003). Furthermore, there was a close correlation between the emergence of N350 and reductions in behavioral responsiveness around sleep onset (Harsh et al, 1994) as well as the emergence of theta activity in stage 1 sleep (Gora et al, 1999;Colrain et al, 2000a).…”
Section: Discussionmentioning
confidence: 86%
“…These components can be related to the sleep facilitation and protection processes, just as the P220, which is also a relatively independent component during sleep. Kállai et al (2003) also state that the sleep-peaking N350, has no information transferring properties. N350 and N550 are just excitatory Fig.…”
Section: Discussionmentioning
confidence: 99%